Comparison of students' perception of problem‐based learning and traditional teaching method in a Nigerian dental school. (6th December 2019) - Oderinu, Olabisi H.; Adegbulugbe, Ilemobade C.; Orenuga, Omolola. O.; Butali, Azeez
Abstract: Objectives: To evaluate the perceptions of dental students on problem‐based learning, PBL, in comparison with the traditional lecture (TL) method. Methods: This comparative study was conducted amongst 72 dental undergraduates. PBL was introduced to the students before the commencement of course. PBL method was used by the student to learn about cariology, whilst other lecture topics were taught by the TL. Students were not informed at the beginning of the course about end of course assessment of learning and teaching methods to limit their bias. The study was approved by the institution's ethics committee, and informed consent was obtained from participants at the end of the course to recruit them into the study. The students worked in small groups to solve tasks on clinical case scenarios. Four class sessions were held for presentations and discussions. The students' perceptions concerning the two teaching methods were sought by the use of an anonymously completed questionnaire. Six perceived factors that influenced the teaching and learning process were extracted from the twenty‐two‐perception‐item questionnaire using factor analysis. Paired sample t test was used for comparison of means. Results: The highest mean scores for all six perceived factors were observed in the PBL method. There were statistically significant differences ( P < .05) between PBL and TL teaching methods for all the perceived factors; ("Challenge critical thinking, " "Communication with peers, " "Usefulness as pedagogical method, " "Organization" and "Interaction between students and tutors") except for the perceived factor "Adequacy of teaching." The mean for most of the perception items was highest in the PBL method compared to TL. The perception item "Able to provide intellectual stimulation" had the highest mean score (4.21 ± 0.76) for the PBL method, whilst it was "Laboratory exercise" (4.14 ± 0.68) for TL. Conclusions: Students' perception of the two educational methods investigated showed a preference for the PBL method. The students felt that PBL provided a higher ability for intellectual stimulation.